Climate, Society and Elemental Insurance Capacities and Limitations - Booth, Kate; Lucas, Chloe; French, Shaun (Taylor & Francis, 2022)
In this book, world-leading social scientists come together to provide original insights on the capacities and limitations of insurance in a changing world. Climate change is fundamentally changing the ways we insure, and the ways we think about insurance. This book moves beyond traditional economics and financial understandings of insurance to address the social and geopolitical dimensions of this powerful and pervasive part of contemporary life. Insurance shapes material and social realities, and is shaped by them in turn. The contributing authors of this book show how insurance constitutes and is constituted through the traditional elements of earth, water, air, fire, and the novel element of big data. The applied and theoretical insights presented through this novel elemental approach reveal that insurance is more dynamic, multifaceted, and spatially variegated than commonly imagined. This book is an authoritative source on the capacities and limitations of insurance. It is a go-to reference for researchers and students in the social sciences - particularly those with an interest in economics and finance, and how these intersect with geography, politics, and society. It is also relevant for those in the disaster, environmental, health, natural, and social sciences who are interested in the role of insurance in addressing risk, resilience, and adaptation.